THE EFFECTIVENESS OF APP-BASED APPROACH TO LANGUAGE LEARNING - Шевченко, Ольга; Огурцова, Ольга (SWorldJournal, 2024)
During the last few years Artificial Intelligence (AI) technologies have transformed traditional language teaching by offering new methods and solutions. Some popular language learning apps, such as Duolingo, Babbel, Rosetta Stone and others now offer pe